2023
DOI: 10.1590/s1677-5538.ibju.2023.9901
|View full text |Cite
|
Sign up to set email alerts
|

Changes in male sexuality after urologic cancer: a narrative review

Abstract: Objective To describe the most common sexual problems and changes experienced by male urological cancer survivors, focusing on evidence-based practices for assessment and intervention. Materials and Methods We search the PubMed, Embase, and SciELO databases between 1994 and 2022, using the following key words: “urological cancer”, “urological malignances”, “genitourinary cancer”, “male sexual health”, and “male sexual dysfunction”. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The quality of life also decreased accordingly. Meanwhile, the severity of FCR in patients also has changed over time ( 15 , 16 ). Cancer patients are becoming increasingly aware of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life also decreased accordingly. Meanwhile, the severity of FCR in patients also has changed over time ( 15 , 16 ). Cancer patients are becoming increasingly aware of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that loneliness is elevated in urological cancer patients, more attention should be given to these patients, and the improvement of psychological management is warranted. In addition, urological cancer patients bear huge financial stress and worry about their physical functions and tumor advancement, which impairs their spiritual well-being ( 24 - 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the study is to evaluate the relationship between anxiety, depression, urinary continence, and recovery of erectile function in patients undergoing radical prostatectomy (RP). It has been observed that the mere diagnosis of cancer can negatively impact male sexual function [7]. In addition, subsequent hospital visits and pre-and post-operative treatments are a source of psychological tension, anxiety, and a sense of loss of male identity.…”
Section: Introductionmentioning
confidence: 99%